Hubungan antara Big Five Personalty dan Religiusitas dengan Subjective Well-being Karyawan - Karim, Sukri (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2017)
This study aimed to find out the correlation between the big five personality and religiosity and the employeeâ subjective well-being in the University Muhammadiyah Malang. This was a correlational study with fifty-five employees as the subject of the study. The data of this study were collected through the big five inventory, religiosity scale, and well-being scale. The data of this study were analyzed by using Spearman correlation non-parametric statistical test and product moment correlation parametric statistical test. The result of this study showed that the big five personality, particularly extraversion, openness and religiosity correlated with the subjective well-being, while agreeableness, conscientiousness, and neuroticism did not correlate with the well-being.Â  This study found that the more the employee leads to extraversion and openness, the better level of well being they have, and the higher religiosity felt by the employee, the higher well-being they will feel. The result of this study gives an alternative policy for the Institution in increasing the employeeâ well-being.Â  Developing the employeeâ religiosity and big five personality can increase the employeeâ well-being